Impact of diabetes mellitus on female subjects undergoing transcatheter aortic valve implantation: Insights from the WIN-TAVI international registry. (1st January 2021) - Goel, Ridhima; Sartori, Samantha; Cao, Davide; Claessen, Bimmer E.; Baber, Usman; Chandiramani, Rishi; Nicolas, Johny; Roumeliotis, Anastasios; Power, David; Chandrasekhar, Jaya; Tchetche, Didier; Petronio, Anna Sonia; et al.
Abstract: Background: Female subjects constitute half of all transcatheter aortic valve implantation (TAVI) candidates, but the association between important comorbidities such as diabetes mellitus (DM) and clinical outcomes after TAVI remains unclear in this group. Method: WIN-TAVI is a real-world international registry of exclusively female subjects undergoing TAVI. The study population was stratified into those with (DM) and those without DM (NDM). Valve Academic Research Consortium (VARC)-2 efficacy (composite of all-cause death, stroke, myocardial infarction, hospitalization for valve-related symptoms or worsening congestive heart failure, or valve-related dysfunction) was the primary endpoint for this analysis. Results: Of the 1012 subjects included in this study, 264 (26.1%) had DM at baseline. DM patients were younger but had a higher burden of comorbidities. There were no differences in VARC-2 efficacy events between DM and NDM patients at 30 days or 1 year. Conversely, patients with DM had a lower risk of VARC-2 life threatening bleeding at 30 days and 1 year after TAVI compared to NDM patients, which remained significant even after multivariable adjustment (HR, 0.34, 95% CI, 0.12–0.99; p  = .047). In the subgroup analysis, insulin-dependent DM was not associated with an increased risk of adverse outcomes. Conclusions: Among female patients undergoing TAVI, more than one-fourth of the subjects presented with DM. At 1-year follow-up, DM was associated with lower bleeding complications and no increase in the risk of other adverse events, including mortality, after TAVI. Graphical abstract: Unlabelled Image Highlights: One fourth of female subjects undergoing transcatheter aortic valve implantation have diabetes mellitus at baseline. DM female patients undergoing TAVI have higher comorbidities and lower transvalvular gradients. DM in female subjects is associated with lower risk of VARC-2 life threatening bleeding up to 1 year after TAVI.